Bill Cosby on Twitter and Beyond - Assmann, Karin (AoIR Selected Papers of Internet Research, 2016)
When a video of comedian Hannibal Buress calling entertainer Bill Cosby a rapist went viral in October 2014, journalists were quick to explain why they had not pursued these rape allegations much earlier. “The absence of social media in 2005” was one of the reasons they gave for dropping the story when Cosby was first charged. This paper examines what features of the discourse on social media made Bill Cosby a newsworthy topic in 2014 in the view of the mainstream news media. A content analysis of tweets on the day the tide of public opinion turned against Cosby and an analysis of the follower networks of influencers who brought voices critical of the comedian out of the Twitter sphere into the mainstream newsrooms, contributes to an understanding of the dynamic of gatekeeping on social media networks and the new, perhaps weakened role of traditional news media outlets as agenda-setters.